2007
DOI: 10.1080/10428190701411441
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab-related viral infections in lymphoma patients

Abstract: Recently, a human/mouse chimeric monoclonal antibody, rituximab, has been successfully used to treat cases of B-cell non-Hodgkin's lymphoma and some autoimmune diseases. However, several viral infections related to rituximab have been reported in the literature, but were not well characterized. To further investigate this topic, relevant English language studies were identified through Medline. There were 64 previously reported cases of serious viral infection after rituximab treatment. The median age of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
179
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(185 citation statements)
references
References 55 publications
1
179
2
3
Order By: Relevance
“…There was no significant difference between TN and NTN patients regarding mean age (52.3 vs 53.4). In a published, small cohort study in Turkey, mean age was reported as 44 among TN patients and 47.5 among NT patients; however, the difference was not significant (Aksoy et al, 2007). The mean age of patients with TN breast cancer is reported as 61 among American patients, and 50 among Hispanic women (SEER, 2010;LaraMedina et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference between TN and NTN patients regarding mean age (52.3 vs 53.4). In a published, small cohort study in Turkey, mean age was reported as 44 among TN patients and 47.5 among NT patients; however, the difference was not significant (Aksoy et al, 2007). The mean age of patients with TN breast cancer is reported as 61 among American patients, and 50 among Hispanic women (SEER, 2010;LaraMedina et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rituximab has a well-established safety profile through its use in haemato-oncological indications for over 10 years (Kimby, 2005). Physicians should be aware, however, that rituximab has been associated with rare cases of progressive multifocal encephalopathy, hepatitis B reactivation and other viral infections in NHL (Goldberg et al, 2002;Steurer et al, 2003;Aksoy et al, 2007;Freim Wahl et al, 2007;Kranick et al, 2007).…”
mentioning
confidence: 99%
“…Cependant, dans tous ces cas d'infections virales, y compris pour l'infection à JC virus, le rituximab était prescrit en association avec d'autres molécules ou immunosuppresseurs, interdisant toute conclusion. Des réactivations virales dues au virus de l'hépatite B (HBV) ont également été rapportées sous rituximab [18][19][20][21] avec un risque de décès important [22]. Dans les quelques cas où le rituximab a entraîné une agammaglobulinémie, des infections bactériennes muqueuses ont été observées, requérant des traitements substitutifs par immunoglobulines polyvalentes [9,23].…”
Section: Anti-cd20 : Rituximabunclassified